The protective effects of alpha-pinene on high glucose-induced oxidative stress and inflammation in HepG2 cells - Razieh Choghakhori; Mozhgan Azadpour; Amir Abbasnezhad; Farzad Ebrahimzadeh; Hassan Ahmadvand (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): Hyperglycemia, a prevalent metabolic condition observed in diabetes, leads to oxidative damage, inflammatory responses, and other consequences. Natural compounds alleviate the adverse impacts of diabetes. We aimed to explore the effects of alpha-pinene (AP) as a monoterpene on oxidative damage and inflammation caused by high glucose (HG) in the human hepatocellular liver carcinoma (HepG2) cell line. Materials and Methods: The HepG2 cells were subjected to non or HG concentration (50 mM) and treated with or without AP (8, 16, and 32 μg/ml) for 48 hr. The effect of treatments on cellular viability, malondialdehyde (MDA), glutathione (GSH), and activity of anti-oxidant enzymes, including glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), was determined. The gene expression levels of nuclear factor-κβ (NF-κB), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and dipeptidyl peptidase-4 (DPP-4) were estimated using quantitative real-time polymerase chain reaction (qRT-PCR). Results: HG exposure significantly increased cell death, MDA formation, and depletion of GSH content and GPx, CAT, and SOD activity (P<0.05). We have also seen a significant induction in NF-κB, TNF-α, IL-6, and DPP-4 gene expression in hepatocytes under HG conditions (P<0.05). Interestingly, co-treatment with AP in a dose-dependent manner improved cell death and altered levels of MDA and GSH, and activity of GPx and CAT (P<0.05). AP could also modulate the gene expression of NF-κB and inflammatory biomarkers dose-dependently (P<0.05). Conclusion: Our findings suggested the protective effect of AP on hepatocytes under HG conditions through attenuating oxidative stress markers and suppression of inflammatory pathways.